UV-B radiation reduces in vitro germination of Metarhizium anisopliae s.l. but does not affect virulence in fungustreated Aedes aegypti adults and development on dead mosquitoes - Falvo, Marianel Lucía (2016)
Fil: Falvo, Marianel Lucía. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Estudios Parasitológicos y de Vectores; Argentina